A study of drug utilization trends in acute coronary syndrome in intensive cardiac care unit at a tertiary care hospital, Mysore - Lakshmi, Saranya Kalyanasundarram; Gowda, Hema Narasimhe; Sadananda, Kanchanahalli Siddegowda (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Acute Coronary Syndrome (ACS) is an emergency condition where usage of many drugs during its management in ICCU is common. This could be a potential cause for Polypharmacy, Potential Drug-Drug Interactions and increased Cost Burden on patients. The objective of the study was WHO criteria for prescription like, 1) Average number of drugs per prescription, 2) Percentage of drugs prescribed by Generic name, 3) Percentage of drugs with Injections prescribed, 4) Percentage of prescriptions with Antibiotics and 5) Percentage of drugs prescribed from the WHO Essential Drugs List. Methods: After obtaining approval from Institutional Ethics Committee, an observational study was carried out among 125 patients in a tertiary care hospital, Mysore. Patients diagnosed with ACS admitted in Intensive Cardiac Care Unit (ICCU) for initial 48 hrs were included in the study. The prescriptions were analyzed for WHO criteria for prescription. The results were analyzed using Descriptive Statistics and T- test. Results: In our present study the most common diagnoses were found to be ACS- Anterior wall myocardial infarction (36.8%) and ACS-Inferior wall myocardial infarction (32.8%). Hypertension (35.2%) and Type 2 diabetes mellitus (29.6%) were the frequently associated co-morbid conditions. Antiplatelet drugs (100%) and Hypolipidemic drugs (100%) were the most commonly prescribed, followed by Anti coagulants (94.4%). The average number of drugs per prescription was 9.09±2.17. Percentage of drugs prescribed by generic names was 37.29%. The percentage of drugs prescribed from essential drug list was 50.84%. Conclusions: The present study provides valuable insight about the overall pattern of drugs used in Acute Coronary syndrome. Physician should be encouraged to prescribe drugs with generic name.